The effectiveness of the teaching methodologies in audit education: A student perspective - de Villiers, Rikus Ruben; Fouché, Jacobus Paulus (South African Journal of Higher Education, 2016)
Literature supports the fact that the approach followed in audit education is in need of improvement. This study highlighted the fact that current teaching methodologies employed by audit lecturers are not assisting audit students to master the various inherent requirements of their field of work. The primary objective of this study was to evaluate whether the current teaching methods followed in audit education at universities accredited with the South African Institute of Chartered Accountants (SAICA) enables students to master the auditing and assurance competencies stipulated by the SAICA in their competency framework. This was achieved through statistical analysis of data gathered from undergraduate chartered accountancy audit students at two SAICA-accredited South African universities, using a questionnaire that was developed for this purpose. The results showed that there is room for improvement in the methods applied by audit lecturers in the audit classroom. The article concludes with recommendations for improvement and future research, followed by a statement on the limitations of the study.